Analysis of androgen receptor and anti-Müllerian hormone pathways in human granulosa cells under luteinizing hormone treatment - Lan, Kuo-Chung (BioMed Central, 2013)
BACKGROUND: The objective of this study was to determine the gene expression profiles of the androgen/androgen receptor (AR) and anti-Müllerian hormone (AMH)/ Sry-related high-mobility group box 9 (SOX9) pathways in granulosa-luteal cells from patients undergoing standard in vitro fertilization (IVF) with or without recombinant luteinizing hormone (rLH) therapy. METHODS: Levels of reproductive hormones in the pre-ovulatory follicular fluid and the expression levels of LHR (luteinizing hormone receptor), AR, SOX9, AMH, AR-associated protein 54(ARA54)and ARA70 were determined in granulosa-luteal cells by real-time reverse-transcription PCR. The effects of androgen and rLH treatments on AR and AMH expression levels were also tested in vitro using HO23 cells. RESULTS: We collected 35 an 70 granulosa cell samples from patients cycled with and without rLH supplementation, respectively. The clinical outcomes were similar in patients who received rLH therapy and those who did not, though the pre-ovulatory follicular fluid levels of androstenedione, testosterone, and estradiol were significantly higher and progesterone was lower in the rLH supplementation group. Moreover, granulosa-luteal cell mRNA levels of LHR, AR, AMH, and SOX9 were significantly higher in the rLH supplementation group relative to the group that did not receive rLH supplementation. In addition, we observed significant correlations between LHR and AR mRNA expression and among AR, AMH, and SOX9 mRNA expression in granulosa-luteal cells from patients undergoing standard IVF treatment. CONCLUSIONS: Increased expression of LHR, AR, AMH, and SOX9 is characteristic of granulosa-luteal cells from IVF/ intracytoplasmic sperm injection (ICSI) patients receiving rLH supplementation.